Metadherin contribute to BCR signaling in chronic lymphocytic leukemia - Li, Pei-Pei (e-Century Publishing Corporation, 2014)
We have reported Metadherin (MTDH) was proven to be overexpression and involved in malignance of chronic lymphocytic leukemia (CLL) via Wnt signaling pathway. In this study, we further investigate the role of MTDH in regulation of BCR signaling pathway in CLL. Six CLL samples whose cells were proliferation after BCR activation were chosen from patients with unmutated IgVH. CCK-8 method used to evaluate the proliferation rate. MTDH expression was measured by quantitative PCR and Western blot. After BCR activation, there exist upregulation of MTDH expression in mRNA and protein level in all six CLL patients (P<0.05). In cell line MEC-1, we observed the same pro-proliferation effect accompanying with elevated MTDH expression. The proliferation effects of BCR activation to MEC-1 can be inhibited by MTDH interference. The results of this study indicate that MTDH involved in the pro-proliferation effect of BCR activation in CLL. And the results imply that MTDH can be a potential therapy target of CLL.